Age-related effects on fitness performance in elite-level soccer referees - Castagna, C.; Abt, G.; D'Ottavio, S.; Weston, M. (The Journal of Strength and Conditioning Research, 2005)
Elite soccer referees usually achieve the peak of their officiating careers at an average age that is considerably older than that observed in competitive matched soccer players. As ageing has been reported to negatively affect physical performance, the aim of this study was to investigate the effect of ageing on fitness performance in elite-level soccer referees. Thirty-six elite-level soccer referees were grouped into young (Y, n = 12), average (A, n = 14), and old (O, n = 10) groups, according to their age and observed for field test performance (countermovement jump [CMJ], 50-m and 200-m sprints, and 12-minute running for distance). Results showed a significant age effect on CMJ (r = -0.52, p < 0.001), 200 m (r = 0.51, p < 0.001), and 12-minute time trial running (r = ?0.52, p < 0.001). Y jumped higher than A and O groups (p < 0.05) and were faster than O over 200 m (p < 0.05). No group effect was observed for 12-minute run and 50-m performance (p > 0.05), respectively. Sixteen of the 36 referees were further examined for selected physiological variables and grouped into 2 equal (n = 8) age groups (young and old, Y1 and O1, respectively). VO2max was higher in Y1 (p < 0.05), but O1 attained performances similar to Y1 running at selected blood lactate speeds (4 mmol L-1, p > 0.05). Although older referees demonstrated acceptable fitness levels, younger officials should ensure that they develop appropriate levels of aerobic and anaerobic fitness to be able to match the demands placed upon them while refereeing throughout their careers. To promote this, fitness test standards should be age related.